Meningkatkan Hasil Belajar Volume Balok dengan Model Pembelajaran PBL serta NHT - Candra; Sunarno (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This study aims improve student learning outcomes PBL and NHT models in grade V SDN Lok Rawa Barito Kuala, this study involved 14 students. This study uses Classroom Action Research Technique which qualitative approach for two cycles. The information used qualitative information measurable observation of student and teacher participation in educational activities, information form of learning outcomes obtained by individual written tests end cycle. According to the results study, teacher activity scored 21 with the "Good" criterion in first cycle and rose to score of 26 with "Very Good" criterion in second cycle. First cycle, student participation was 54%; in the second cycle, it rose to 85%. In cycle I, the learning outcomes students in the cognitive domain were 15%; in cycle II, it rose to 92%. Given the findings research, learning PBL and NHT mathematics from block volume materials, can improve student activities, teacher activities, and student learning outcomes.